The Jesus of K Road: Theological reflections on Māori and homelessness - Rangiwai, Byron (Te Kaharoa, 2021)
This paper reflects on my observations of, and casual discussions with, Māori experiencing homelessness, specifically, during the current lockdown in Auckland which began on 17 August 2021. It is important for those who experience homelessness to have their voices heard (Beaton et al., 2015). Amplifying these voices could increase understanding of the very complex issues that are faced (Beaton et al., 2015).